Steven/Sherry Pilkington - Amy Holthouser (Association of American Medical Colleges, 2008)
Abstract Introduction This resource is a problem-based learning (PBL) case that takes place in the context of a 2-year team-based learning cases course titled Interdisciplinary Clinical Cases. This case is designed to teach second-year medical students a rational approach to the diagnosis of an infant of different ages (15 days, 75 days, and 30 months) with a fever of unknown source. Methods Students work in subgroups to research the answer to study questions prior to the case that links their knowledge of pathology and microbiology/immunology with the clinical sciences. The use of Prevnar and haemophilus influenzae type B vaccines is reviewed and applied to the patients so students understand the differences in treating vaccinated, immune-competent patients. Unique characteristics of infants are explored as well as the most common serious bacterial infections in this patient population. Evidence-based recommended treatment guidelines from Cincinnati Children's hospital for patients with fever of unknown sources in these age groups are critically reviewed and applied. A standardized patient (SP) script for the parent of the child is included, but could be given to learners if no SP is available to act as the parent. Results Students appreciated learning a clinically relevant way to think about vaccines and their effect on medical decision-making in simulated patients. Discussion It is difficult for even the brightest students to apply knowledge about required vaccines to a patient scenario; this is what makes the case effective as a teaching tool. It is optimal, but not necessary, to have a SP involved as the parent of the child.